Research of Inonotus obliquus Oligosaccharide in Prevention of Hyperlipidemia - Dawei Wu; Yanrong Zhang; Dawei Wang; Tingting Liu; Shanshan Zhang; Chenhe Yang (Journal of Food Quality)
In this study, hot water was used to extract Inonotus obliquus oligosaccharide. DEAE-cellulose and Sepharose G-200 were used to purify Inonotus obliquus oligosaccharide. Inonotus obliquus oligosaccharide IOP-2A was obtained. Its molecular weight Mw is about 1000 Da. The monosaccharide composition and molar ratio were glucose : xylose : galactose : mannose = 54.1 : 13.6 : 13.2 : 6.7. In addition, it also contains a small amount of galactose, gluconic acid, rhamnose, and fucose. IOP-2A contained mainly β-glycosidic bonds. Among them, 1,4-glycosidic bonds accounted for 9.2%, and 1,6-glycosidic bonds accounted for 85.1%. Oligosaccharide macromolecules formed a layered structure. Mouse experiments showed that IOP-2A had the function of preventing hyperlipidemia. At the same time, IOP-2A had a certain protective effect on the liver and kidney. The mechanism of IOP-2A in preventing hyperlipidemia was obtained from the perspective of mouse intestinal flora.